Effect of Seeding Date on the Performance of Grasses and Broadleaf Species Evaluated for Cover Crop Management in the Breede River Valley Wine Grape Region of South Africa - Fourie, J.C.; Louw, P.J.E.; Calitz, F.J. (South African Journal of Enology and Viticulture, 2017)
The trial was conducted over a period of two years on a medium-textured soil near Robertson (33°50’S, 19°54’E), situated in the Breede River Valley of the Western Cape. The effect of seeding date on the dry matter production (DMP) and weed control efficacy of eight grasses and sixteen N-fixing broadleaf species, as well as varieties of three of these species, were determined. The decomposition rate of the surface mulches during summer (from the end of August to the end of January) was measured to determine the persistence of the fibre of the different species. Seeding date had a significant effect on most of the species. Triticale v. Usgen 18 (triticale), Avena sativa L. v. Overberg (‘Overberg’ oats), Avena strigosa L. v. Saia (‘Saia’ oats) and Secale cereale L. v. Henog (rye) effectively suppressed the winter-growing weeds of the region and produced more than the five tons of dry matter per hectare deemed necessary for effective cover crop management with a grass species. These species produced the highest amount of dry matter if sown in early April (mid-autumn). Vicia faba L. v. Fiord (faba bean) and Medicago truncatula v. Paraggio (‘Paraggio’ medic) controlled the winter-growing weeds acceptably, while producing more than the six tons of dry matter per hectare suggested to be necessary for the prevention of erosion in most vineyard soils. Vicia dasycarpa Ten. (grazing vetch) suppressed the winter-growing weeds acceptably. Although these legumes did not produce more than the eight tons of dry matter per hectare deemed necessary for effective control of summer growing weeds under intensive full-surface irrigation, they should still be considered for cover crop management on soils with a low organic matter content in the region, because of their ability to supply nitrogen to the grapevines. A highly significant correlation was found between the decomposition rate of the surface mulch and the initial amount of dry matter present on the soil surface.